2016
DOI: 10.14400/jdc.2016.14.8.527
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Factors influencing the Attitudes and Dispositions of Doping in Elite Golf Players

Abstract: The purpose of this study is to identify the factors influencing the attitudes and dispositions of doping in elite golf players. 136 elite golfers (75 male, 61 female) were participated in this study and responded to Performance Enhancement Attitude Scale, Perfectionism in Sport Scale and Perceived Motivational Climate in Sport Questionnaire-2. Data that were collected analyzed by hierarchical multi regression. In male golfers, unequal recognition (UR) of coach had a positive effect on the attitudes and dispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To measure each athlete’s level of perfectionism in the sport, the PSS, proposed by Anshel and Eom [ 33 ] and translated into Korean by Kim et al [ 51 ] was used. The PSS comprises 32 items on a five-point Likert-type scale, ranging from strongly disagree (1) to strongly agree (5) and divided into four sub-scales each including eight statements: parental criticism, coach’s criticism, concern over mistakes, and personal standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure each athlete’s level of perfectionism in the sport, the PSS, proposed by Anshel and Eom [ 33 ] and translated into Korean by Kim et al [ 51 ] was used. The PSS comprises 32 items on a five-point Likert-type scale, ranging from strongly disagree (1) to strongly agree (5) and divided into four sub-scales each including eight statements: parental criticism, coach’s criticism, concern over mistakes, and personal standards.…”
Section: Methodsmentioning
confidence: 99%
“…To assess athletes’ perceptions of the prominent motivational climate goal structures created by their coaches [ 54 ], the PMCSQ-2, proposed by Newton et al [ 55 ] and translated into Korean by Kim et al [ 51 ] was used. The Korean version of PMCSQ-2 was reported as being in a valid and reliable tool for measurement of motivational climate in Korean [ 56 ], and the study of Kim et al [ 51 ] showed that Cronbach’s alpha of the higher-order scales under PMCSQ-2 ranged from 0.72 to 0.88. The PMCSQ-2 consists of 33 items on a five-point Likert-type scale, from strongly disagree (1) to strongly agree (5); it is divided into two higher-order scales, respectively covering ego-involving climate and task-involving climate [ 44 , 55 ].…”
Section: Methodsmentioning
confidence: 99%